THE IMPORTANCE OF DISTANCE LEARNING IN THE DEVELOPMENT OF COGNITIVE COMPETENCIES OF STUDENTS - Mamatov, Dilshod Kodirovich (Educational Research in Universal Sciences, 2023)
In today’s information age and pandemic, it is important to form a distance learning system in higher education institutions. In the education system of many countries, the learning process uses a form of distance learning based on modern information and communication technologies to train quality personnel. The experience of the education system shows that the possibilities for a radical improvement in the quality of personnel through the transformation of the Internet and information and communication technologies into the learning process as a means of acquiring, storing, transferring new knowledge and making practical decisions are expanding. In this regard, the remote organization of classes in engineering graphics using technical means is relevant today. In particular, drawing and descriptive geometry require students to have an active spatial imagination. Because projection is an invisible complex process that cannot be explained orally. In this regard, we will focus on the use of problem learning opportunities in the process of teaching drawing in higher education.